Damage initiation of thermally degraded carbon composites in tension. (October 2018) - Wolfrum, J; Quan, E; Maier, G; Eibl, S
This study focuses on exploring the initial failure of thermally degraded carbon fibre-reinforced polymers. It is the aim of this study to provide deep insight into the damage development and propagation as well as to understand failure mechanisms of thermally degraded composites. Carbon fibre-reinforced polymer panels with different fibre orientations are exposed to heat above maximum operational temperature (up to 200 ℃) for various durations (up to ca. 200 days). Thermal degradation of the material is characterized by scanning electron microscopy and infrared spectroscopy. The onset of the failure in tension is determined by acoustic emission analysis. The results show that the development and propagation of cracks depend on the level of thermal degradation and the fibre orientation relative to the applied load. With increasing thermal degradation, transverse matrix cracking, as the prevailing initiating failure mode, is replaced by crack initiation and propagation in the damaged outermost ply independent of its fibre orientation. Severe thermal matrix degradation is limited to this area, as characterized by infrared spectroscopy. With increasing thermal degradation of the polymer matrix, the onset of crack initiation and propagation is shifted to lower strains. The effects of damage initiation on fracture behaviour are discussed.